2007
DOI: 10.1002/ijc.22564
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of genetically tagged chromosome break sequences reveals new fragile sites at 6p21 and 13q22

Abstract: Fragile sites are specific genomic loci that are especially prone to chromosome breakage. For the human genome there are 31 rare fragile sites and 88 common fragile sites listed in the National Center for Biotechnology Information database; however, the exact number remains unknown. In this study, unstable DNA sequences, which have been previously tagged with a marker gene, were cloned and provided starting points for the characterization of two aphidicolin inducible common fragile sites. Mapping of these unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…3). Additionally, 52 identified and in parts mapped FS were already published, but not included in the current genome browser versions (13,14,15,16,17,19,23,34). Most of these sites were confirmed in this study which underlines their eligibility to be appreciated as FS.…”
Section: ------------------------------------------------------------supporting
confidence: 51%
See 1 more Smart Citation
“…3). Additionally, 52 identified and in parts mapped FS were already published, but not included in the current genome browser versions (13,14,15,16,17,19,23,34). Most of these sites were confirmed in this study which underlines their eligibility to be appreciated as FS.…”
Section: ------------------------------------------------------------supporting
confidence: 51%
“…Additionally, differences in the observable FS-frequency within different individuals are well known (11,12). Besides these 88 official, database-annotated common FS others were observed and reported, including six recently reported new sites, particularly FRA4F (13), FRA7K (14), FRA6H (15), FRA9G (16), FRA13E (15) and FRA18C (17).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, four novel common fragile sites, FRA4F (Rozier et al, 2004), FRA7K (Helmrich et al, 2007), FRA6H, and FRA13E (Fechter et al, 2007b), which are not recorded in the GDB Human Genome Database, have been identified. In the present study, we report the precise genomic localization of another novel aphidicolin-inducible common fragile site, FRA9G, spanning an 300 kb region at 9p22.2.…”
Section: Discussionmentioning
confidence: 98%
“…However, the exact number of common fragile sites appears to be even larger than those identified by classical cytogenetic analysis. This is documented by the fact that application of high resolution mapping approaches revealed four new common fragile sites in the human genome, FRA4F (Rozier et al, 2004), FRA7K (Helmrich et al, 2007), FRA6H, and FRA13E (Fechter et al, 2007b). Breaks at individual common fragile sites have been found to scatter over large genomic region encompassing hundreds to thousands of kilobases.…”
Section: Introductionmentioning
confidence: 95%
“…Chromosome breakage at CFSs can lead to translocations and gross chromosome terminal deletions after APH treatment in somatic cell hybrid systems in which there is no negative selection for loss of genes distal to the CFS (8,9). CFSs are also preferred sites of integration for transfected DNA in cells pretreated with APH (10)(11)(12) and have been implicated in breakage leading to intrachromosomal gene amplification events in cultured CHO cells (13).…”
mentioning
confidence: 99%